(untitled) (Journal of Applied Learning and Teaching, 2025)
In this article, I demonstrate that the Hindi film Sherni (Masurkar, 2021), Atlanta’s Cop City project, and genocidal violence against Palestinians intertwine in their decolonial possibilities to create an environmentally and anti-war conscious classroom. I have utilized the above-mentioned Hindi film, Atlanta’s environmental concerns, and the war on Palestinians to encourage green mindfulness in an otherwise tech-dominated western academic space. “Cop city” is what activists call a police and fire department training center that is currently under construction. This 90- million police training facility would be one of the largest militarized police training centers in the country—all built by clear-cutting Atlanta’s largest green space. Hence, the project faces massive opposition. It also maintains a relationship with the Israeli Defense Forces, creating an exchange of oppressive mechanisms between the two settler colonial nations. In such a case, I raise a political green consciousness among my students beginning with the Hindi film Sherni, which shows how the rhetoric of expansion, extraction, and land development in a postcolonial world is often based on the erasure of indigenous farming practices, forcible relocation of population from their lands, and recruitment of law, criminals, and political figures to build oppressive regimes. Once the tone is set, discussions on the local issue of cop city and the global case of Palestinian territories help drive the arguments home that colonization is deeply rooted in the erasure and control of natural resources and often a postcolonial nation-state functions through such colonial mechanisms that give rise to intra-national green neocolonialism.